The Meaning of Media Independence by Journalists in the 2024 Election - Gafar Yoedtadi; Ahmad Djunaidi; Yugih Setyanto; Lusia Savitri Setyo Utami (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
The 2024 Presidential Election is a political event that the public has been waiting for. At that time, the public can exercise their political rights to elect government leaders for the next five years. Seeing such great public attention, the mass media will place the 2024 General Election and Presidential Election as one of the main portions of the news. However, like the 2014 and 2019 Presidential Elections and Elections, it is suspected that it will be difficult for the mass media to stand in a neutral position. Mass media, especially television stations, are owned by entrepreneurs who are affiliated with political parties and support the 2024 presidential and vice presidential candidates.This research aims to explain the meaning of television journalists regarding media independence ahead of the 2024 general election and presidential election. This research uses a qualitative approach with phenomenological research method to understand the construction meaning of journalists. The object of this research is the meaning of television journalists regarding media independence ahead of the 2024 general election and presidential election. The research subjects were television journalists from two media groups, MNC Group and Media Group, who were selected purposively. The research data was analyzed using media political economy theory. Findings from the research show differences in the subjective meaning of media independence among television journalists. Although they agree on the urgency of media independence as a guardian of press freedom, differences of opinion arise especially regarding the role of media owners in editorial policy. Some journalists consider the intervention of media owners to be acceptable, while others consider it a violation of the journalistic code of ethics. Different views are also seen in terms of implementing media independence. Some see media independence as the freedom for the media to support political parties or presidential candidates that are in line with the editorial views. On the other hand, there are journalists who believe that media independence should be realized through a neutral and unbiased attitude